Cultural nationalism. A review and annotated bibliography - Eric Taylor Woods (Studies on National Movements, 2014)
This review and annotated bibliography is part of The State of Nationalism (SoN), a comprehensive guide to the study of nationalism. Topic of this first contribution is cultural nationalism. This concept generally refers to ideas and practices that relate to the intended revival of a purported national community's culture. If political nationalism is focused on the achievement of political autonomy, cultural nationalism is focused on the cultivation of a nation.